EVALUATION OF VON WILLEBRAND FACTOR AND ADAMTS13 LEVELS IN MYOCARDIAL INFARCTION PATIENTS COMPARED TO HEALTHY CONTROLS (The Research of Medical Science Review, 2025)
Myocardial infarction is a major cause of morbidity and mortality globally. Abnormality of von Willebrand Factor and cleaving protease ADAMTS13 has been described to induce a prothrombotic condition and hence to play a pathophysiological role in MI. This study was conducted to assess plasma levels of VWF and ADAMTS13 in MI patients versus healthy controls to identify their utility in diagnosing dys and for prognostication. 100 participants were enrolled and VWF and ADAMTS13 analyzed with the use of chromogenic assay and ELISA methods respectively. Statistical analysis showed significantly elevated levels of VWF and decreased ADAMTS13 in MI patients. The VWF/ADAMTS13 imbalance might constitute a new axis of biomarkers for the identification of risk for thrombosis and disease severity in MI. Its clinical and therapeutic usefulness should be confirmed with further studies.